O ensino médio em rede sob o olhar dos diferentes atores de uma comunidade escolar - Menten, Maria Luiza Machado (2007)
The main aim of this analytical and qualitative piece of research was to contribute to the continuing education of secondary school teachers by describing and critically analyzing the repercussions of a Programme, called Ensino Médio em Rede (EMR), used to give continuing education to secondary school teachers at a public state school where I have been working as a full time teacher for seventeen years. The purpose of this piece of research is based on the first phase of this Programme which had been developed at a Secondary State School in the State of São Paulo, from August 2004 to July of 2005. The results were obtained from interviews with teachers, coordinator and technical pedagogical assistant, from participative observations (mainly at school), documents generated by all the participants (evaluation letters from the Programme) at the end of phase 1 (July/2005) and from the material produced for the development of the Programme, like videos, books and CD with complementary text. The central objectives of the research were: 1) To analyze the Programme and its theoretical referencial from a critical perspective; 2) To identify the conceptions of the teachers, the coordinating teacher and of two mediators (a technical pedagogical assistant and a supervisor) about public policies, and more specific, about the Programme; 3) To individualize the movement of its insertion in a public state school under the view of its different involved partners, trying to delineate its repercussions, impacts, controversial subjects, positive points and flaws. From the immediate, chaotic and fragmented view given by official speeches, taken from the material made for the Programme, from participative observations, interviews and evaluation letters, I researched through approximations and successive abstractions carried out through the readings to analyze the collected material, the actual context and the theoretical referential adopted by the Programme (reflexive teacher and competences pedagogy) in a critical perspective. I implemented a dialogue with several researchers that present distint theoretical filiations, but it was possible to analyze the opinions and movements. The data analyses were carried out from a referential in the public policies areas and teacher s continuing education, which enabled me to understand some of the debate made by the teachers, as well as to observe theirs views about the world issues and also with the instigating historical themes within the educational area. In general, all the individuals involved criticized the short time of the institutional collective space (HTPC) to establish the programmed activity. A group of teachers also taunted the proposal supported by the Programme, as well as the lack of an open debate of the other theoretical dimensions. However, its implementation was a progress in the transformation of HTPC in a permanent space for the development of teachers within the school scope. The critical way of some teachers to the Programme proposal was accepted as a political resistant in defense to the public school and also the educational work which can not lose their historical role and their specificity.